Prioritising Alternative Livelihood Options for Fishers of Ratnagiri District, Maharashtra - S. V. Patil; B. M. Yadav; S. S. Mandavkar; S. M. Wasave; M. M. Shirdhankar; K. J. Chaudhari; B. V. Naik; V. G. Yewale (Journal of Indian Fisheries Association, 2021)
Globalization in fisheries and aquaculture has increased the demand for fish and fishery products. This increased demand for fish caused over exploitation of the fisheries resources and brought competition among fisher population for exploiting the depleting fisheries resources for economic gains. The marine capture fish production in the state during last decade indicating more or less stagnation / decreasing trend. Fishers are hit by this depleting fisheries resources bases. This condition warrants rehabilitation of marine fishers through intervention of alternative livelihood options. Hence, present investigation was carried out to prioritise various sustainable alternative livelihood options to the marine fishers of Ratnagiri district, Maharashtra. Information was collected from 100 randomly selected marine fishers (fishers, fishing boat owner, fishing boat crew members, fresh/dry fish seller) whose income source of livelihood was fishing and fishing related allied activities. The weighted average technique was applied to analyse and rank various alternative livelihood options. Basic information was collected by conducting personal interview as well as Focus Group Discussions (FGDs). Results indicated that maximum fishers were boat owner (50%), followed by fishing boat crew members (35.9%), fresh / dry fish seller (12.5%) and others involved in fishing related occupations (1.6%). Crab farming in mangrove area, open sea cage culture, fresh fish selling, Seabass culture, mussel / oyster culture and brackishwater shrimp farming were the prioritised major alternative livelihood options identified for the fishers of Ratnagiri district, Maharashtra. Therefore, Government Organisations like Department of Fisheries (DoF), Fisheries Institutions, Krishi Vigyan Kendra should take necessary steps for skill development of fishers to adopt these identified alternative livelihood generating options.